Relocation of the Hypocenter of an Earthquake with the Double Difference Method in the Mentawai - Hanifah Maulani, Siti; Refrizon, Refrizon; Samdara, Rida; Agung Satria, Lori; Ahadi, Suaidi (JURNAL GEOCELEBES, 2025)
This research aimed to accurately relocate the hypocenter of earthquakes in the Mentawai region to enhance precision in hypocenter determination. The arrival time data used were secondary data recorded in the seiscomp4 software at BMKG Class I Padang Panjang. The dataset comprised 66,979 arrival time data point form 2,380 earthquakes that occurred between September 2023 and September 2024. The Double-difference method, utilizing the Crust 2.0 velocity models, was employed for the relocation process. This method evaluated two hypocenters using a single recording station, provided that the distance between the hypocenters was less than the distance to the recording station. The HypoDD program was used for data processing. The relocation results indicated that the hypocenter had shifted and exhibited an increasing tendency toward cluster formation. The hypocenter depth was adjusted from an initial average of approximately 41.05 km to 51.05 km. This shift suggested am improvement in the quality of residual distribution. The enhancement of earthquake hypocenter resolution supported disaster mitigation by accelerating early warnings, improving construction safety in earthquake-prone areas, and optimizing emergency response. The relocation results in the Mentawai region identified 89 earthquake hypocenter points out of the 94 points recorded before relocation.